Things we lost to the water : a novel - Nguyen, Eric, 1988- (Alfred A. Knopf, 2021)
"When Huong arrives in New Orleans with her two young sons, she is jobless, homeless, and worried about her husband, Cong, who remains in Vietnam. As she and her boys begin to settle into life in America, she continues to send letters and tapes back to Cong, hopeful that they will be reunited and her children will grow up with a father. Over time, Huong realizes she will never see Cong again. While she copes with this loss, her sons, Tuan and Binh, grow up in their absent father's shadow, haunted by a man and a country trapped in their memory and imagination. As they push forward, the three adapt to life in America in different ways: Huong takes up with a Vietnamese car salesman who is also new in town; Tuan tries to connect with his heritage by joining a local Vietnamese gang; and Binh, now going by Ben, embraces his burgeoning sexuality. Their search for identity--as individuals and as a family--tears them apart, until disaster strikes and they must find a new way to come together and honor the ties that bind them"--